2010
DOI: 10.1063/1.3316794
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of amphiphilic peanut-shaped nanoparticles

Abstract: We use computer simulation to investigate the self-assembly of Janus-like amphiphilic peanut-shaped nanoparticles, finding phases of clusters, bilayers and micelles in accord with ideas of packing familiar from the study of molecular surfactants.However, packing arguments do not explain the hierarchical self-assembly dynamics that we observe, nor the coexistence of bilayers and faceted polyhedra. This coexistence suggests that experimental realizations of our model can achieve multipotent assembly of either of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 55 publications
5
40
3
Order By: Relevance
“…They found that, as well as spherical micellar-type structures and wormlike strings, also bilayers and faceted polyhedra were possible as supracolloidal structures. Whitelam and Bon [47] used computer simulations to investigate the self-assembly of Janus-like peanut-shaped nanoparticles and found phases of clusters, bilayers, and nonspherical and spherical micelles, in accordance with a packing parameter that is used conventionally and in analogy to predict the assembled structures for molecular surfactants. They also found faceted polyhedra, a structure not predicted by the packing parameter (see Fig.…”
Section: Self-assembly Of Amphiphilic Particles Driven By the Hydrophmentioning
confidence: 99%
“…They found that, as well as spherical micellar-type structures and wormlike strings, also bilayers and faceted polyhedra were possible as supracolloidal structures. Whitelam and Bon [47] used computer simulations to investigate the self-assembly of Janus-like peanut-shaped nanoparticles and found phases of clusters, bilayers, and nonspherical and spherical micelles, in accordance with a packing parameter that is used conventionally and in analogy to predict the assembled structures for molecular surfactants. They also found faceted polyhedra, a structure not predicted by the packing parameter (see Fig.…”
Section: Self-assembly Of Amphiphilic Particles Driven By the Hydrophmentioning
confidence: 99%
“…In our case, the weight fraction of hydrophilic PEG in PEG and PNIPAM was 30%, and the ratio of the number of PEG to the number of nanoparticles was three, so we hypothesized that the amphiphilic HIC would lead to vesicles above the LCST of PNIPAM. Figure 1 shows the morphology of HIC at 37 • C. In the transmission electron microscopy (TEM) image ( figure 1(a)), one can see an obvious contrast between the interior and the shell of the particles, which was a characteristic image of hollow spheres as reported [16][17][18][19][20][21]. At a higher magnification, closely attached individual nanoparticles on the shell were visible, demonstrating that the vesicles were actually composed of individual AuNPs.…”
Section: Resultsmentioning
confidence: 86%
“…So far, most applications have used colloidal AuNPs made of ligandstabilized water-soluble gold crystallites [13][14][15]. Vesicular gold aggregates, although they have advantages as a vector of drug delivery and a prototype of living cells, have been reported only very recently [16][17][18][19][20][21]. More significantly, applications of gold vesicles have seldom been explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corresponding dumbbells consist of two colloidal spheres with different sizes or dissimilar materials [2]. Many studies have investigated the self-assembly of colloidal dumbbells into more complex structures, including micelles, vesicles [3,4], bilayers [5][6][7] and dumbbell crystals [8][9][10]. Particularly, open clusters of colloidal dumbbells with syndiotactic, chiral [11,12] and stringlike structures [13] are significant because they can be regarded as colloidal molecules [14,15] that exhibit unique magnetic, optical and rheological properties [16].…”
Section: Introductionmentioning
confidence: 99%